Manajemen Pembinaan Akhlak Siswa Berbasis Pesantren di SMP VIP Al Huda Kutosari Kebumen - Fatimatuz zahra (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2022)
This research the management of morals in SMP VIP Al Huda Kebumen, which is one of the schools based on Islamic boarding school. This research is conducted with qualitative approach.. Technique of collecting data from this research using observation method, interview, and documentation. The results of this study indicate that, Student morality planning is done starting from the formulation of school vision and mission, the selection of students who enter in the school. Organizing in the form of stewardship structure in schools and boarding schools. 3) Implementation of morality of students is done through intra-curricular activity that is the integration of character education / character based on Islamic values into all subjects. Implementation of extracurricular activities with the implantation of Islamic teachings values. The establishment of Islamic culture in the school environment is also supported by the creation of a conducive school atmosphere. 4) Evaluation of student morals through monthly meetings, quarterly and semester meetings.